Catalytic Deoxygenation of Palm Oil Over Iron Phosphide Supported on Nanoporous Carbon Derived from Vinasse Waste for Green Diesel Production - Phetcharat Nenyoo; Peerawat Wongsurakul; Worapon Kiatkittipong; Napat Kaewtrakulchai; Atthapon Srifa; Apiluck Eiad-Ua; Suttichai Assabumrungrat (My University, 2024)
The vinasse waste was effectively converted to nanoporous carbon (NPC) via hydrothermal carbonization with potassium hydroxide (KOH) activation. The nanoporous carbon (NPC) exhibited a maximum surface area of 1018 m
Keywords: Deoxygenation; Vinasse; Vegetable oil refining; Catalysis and Hydrodesulfurization Studies